A tripartite frontier: funding the church of the Nazarene medical mission, 1911-1939 - Ndlangamandla, BR (Vestiges: Traces of Record, 2015)
Couched within the context of social history of medicine, this study explores the trajectory of the Church of the Nazarene medical mission from 1911, when the Nazarene missionaries experienced their first ‘surgical’ service, to 1939 when the Church of the Nazarene had established a medical unit. The absence of large- scale biomedical facilities for the Swazi gave the Nazarene Christian missionaries the impression that they had a health burden to carry. How to fund the Nazarene frontier medical mission was the question that brought the church, the state, and the Swazi together. The study purports to discuss the tripartite funding of the Nazarene biomedical mission using information obtained from the Church of the Nazarene documents and government annual reports housed in the Swaziland National Archives. The significance of this ground- breaking study lies in its ability to evince the subtle nuances of the trajectory of multiple Christian medical mission encounters through the prism of multi- sectoral funding. Resume: Encadrée dans le domaine de l'histoire sociale de la médecine, cette étude explore la trajectoire de l'Église de la mission médicale Nazaréen de 1911, quand les missionnaires nazaréens expérimentés ont entrepris leur première intervention «chirurgicale », jusqu’à 1939, année au cours de laquelle l'Église des Nazaréens a installé   une unité médicale. Les missionnaires chrétiens nazaréens estimaient qu'ils avaient un devoir médical à assurer à l’égard des Swazi qui étaient dépourvus de toutes infrastructures  biomédicales. La question de savoir comment financer la mission médicale nazaréenne outre-mer a été la principale préoccupation de cette église, de l’État et des Swazi eux-mêmes.   La présente étude examine le financement tripartite de la mission biomédicale nazaréenne, en utilisant des sources missionnaires et des rapports annuels officiels  disponibles aux Archives nationales du Swaziland. L'importance de cette étude réside dans la capacité des uns et des autres  à inventer des initiatives novatrices, incluant une approche multisectorielle dans la recherche du financement de la Mission médicale chrétienne au Swaziland.